2019
DOI: 10.1016/j.hjc.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of characteristics of angina symptoms for the prediction of coronary artery disease in a cohort of stable patients in the modern era

Abstract: In a contemporary cohort of patients referred for coronary angiography for stable CAD, the presence of typical angina symptoms was the most important independent predictor of obstructive CAD. The association of atypical angina symptoms with low CAD prevalence compared to nonangina chest pain or absence of significant symptoms probably reflects different management and referral strategies in these groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
6
0
6
Order By: Relevance
“…In a cohort of 686 consecutive patients undergoing diagnostic coronary angiography for suspected CAD, Nakas et al showed that 45.92% had obstructive coronary artery disease. In this study, existence of significant CAD was defined as ≥50% stenosis in the lumen/internal diameter of at least one coronary artery or ≥30% for the left main coronary artery [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 686 consecutive patients undergoing diagnostic coronary angiography for suspected CAD, Nakas et al showed that 45.92% had obstructive coronary artery disease. In this study, existence of significant CAD was defined as ≥50% stenosis in the lumen/internal diameter of at least one coronary artery or ≥30% for the left main coronary artery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Учитывая все эти ограничения, хотелось бы получить подтверждение полученных результатов в какомлибо еще исследовании. В прошедшем году появилась публикация работы Nakas G, et al [16], целью которой было изучить ассоциацию характеристики боли в грудной клетке и различных факторов риска с наличием обструктивных поражений КА среди стабильных больных с подозрением на ИБС, которым проведена КАГ. Было показано, что симптомы типичной стенокардии были ассоциированы с более высокой частотой выявления обструктивной ИБС (ОР 3,47; p<0,001), в то время как при атипичных ангинальных симптомах отмечалось обратное соотношение (ОР 0,49; p=0,003) по сравнению с больными с неангинальными болями или асимптомными.…”
Section: роль клинической оценки в диагностике ибсunclassified
“…При мультивариантном анализе типичная стенокардия оставалась независимым предиктором обструктивных поражений КА (ОР 2,54; p<0,001) с большей предсказательной точностью по сравнению с другими клиническими факторами (AUC 0,715; p<0,001) и схожей по значимости с С-реактивным белком высокой чувствительности (AUC 0,712; p<0,001). Комбинация всех изученных факторов способствовала дальнейшему повышению предсказательной точности (AUC 0,81; p<0,001) [16]. На первый взгляд, данные результаты также свидетельствуют в пользу высокой диагностической значимости именно клинической оценки пациента.…”
Section: роль клинической оценки в диагностике ибсunclassified
See 2 more Smart Citations